Eksplorasi Pengalaman Remaja dalam Pemanfaatan Program Pik-R (Pusat Informasi dan Konseling-Remaja) di Sekolah - Ni Komang Tri Agustini; Ida Ayu Ningrat Pangruating Diyu (Universitas Malahayati Lampung, 2022)
ABSTRACT Adolescents have greater risk to face sexual and reproductive health problems. This is Government had developed health programs for adolescents, Youth Information and Counseling Program for adolescent in school. This activity has been socialized to schools, but its utilization has not been as expected. This study was conducted to explore students' experiences in using PIK-R services in schools with the aim of being able to explore students' experiences in using PIK-R services in schools. The research used is a qualitative method with an exploratory approach to 6 adolescent student participants. Data collection by in-depth interviews. The instrument used is a blend of unstructured interviews. Data analysis used is manual by using data stages according to Colaizzi. Data triangulation, member checking and peer debriefing are carried out to obtain data validity. Adolescent’s experiences consist of three themes, Different perspectives between adolescent curiosity and taboo views in society, The need for trusted services and confidentiality is maintained and Barriers to the implementation of reproductive health services. The use of PIK-R reproductive health services in schools has been utilized by adolescent students, but implementation there are activity can be developed, the counselors, and coordination of related parties. Keywords : Experiences, Youth Information and Counseling (PIK-R), Adolescent ABSTRAK Remaja sangat berisiko untuk menghadapi masalah kesehatan seksual dan reproduksi. Hal ini menjadi alasan pemerintah mengadakan program kesehatan untuk remaja, salah satunya adalah PIK-R. Kegiatan ini telah disosialisasikan ke sekolah-sekolah, namun pemanfaatan nya belum sesuai harapan. Penelitian ini dilakukan untuk menggali pengalaman siswa dalam pemanfaatan layanan PIK-R di sekolah dengan tujuan mampu mengeksplorasi pengalaman siswa dalam pemanfaatan layanan PIK-R di sekolah. Penelitian yang digunakan adalah metode kualitatif dengan pendekatan eksploratif pada 6 partisipan siswa remaja. Pengumpulan data dengan wawancara mendalam. Instrumen yang digunakan adalah paduan wawancara tidak terstruktur. Analisa data digunakan adalah manual dengan menggunakan tahapan data menurut Collaizi. Triangulasi data, member checking dan peer debriefing dilakukan untuk memperoleh keabsahan data. Temuan dalam penelitian ini adalah Perspektif berbeda antara keingintahuan remaja dengan pandangan tabu di masyarakat, Kebutuhan pelayanan yang terpercaya dan kerahasiaan terjaga dan Hambatan pelaksanaan pelayanan kesehatan reproduksi. Pemanfaatan layanan kesehatan reproduksi PIK-R disekolah telah dimanfaatkan oleh siswa remaja, namun dalam pelaksanaannya ada beberapa hal yang harus dibenahi seperti jenis pelayanan yang diberikan, petugas yang bertugas di PIK-R dan koordinasi pihak terkait untuk rencana tindak lanjut Kata Kunci: Pengalaman, PIK-R, Remaja